2001
DOI: 10.1002/ijc.10179
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of HER‐2/neu overexpression relating to HLA haplotype in patients with gastric cancer

Abstract: We have identified that HER-2/neu-derived peptides are naturally processed as tumor rejection antigens recognized by tumor-specific, HLA-A2-restricted cytotoxic T lymphocytes in gastric cancer. To evaluate candidates for immunotherapy using HER-2/neu-derived, HLA-A2-restricted peptides, we examined the frequency of HLA-A2 relating to HER-2/neu overexpression or the infiltrating grade of tumorinfiltrating lymphocytes (TILs) in Japanese patients with gastric cancer. HER-2/neu-overexpressing tumors detected by im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 31 publications
(32 reference statements)
1
15
0
1
Order By: Relevance
“…When anti-HER-2 immunotherapy such as cancer vaccination is considered for HER-2-positive patients, the candidates are restricted to a certain HLA haplotype (Kono et al, 2002a). It is important to clarify the HER-2 status relating to the HLA haplotype in patients with oesophageal SCC.…”
Section: Correlation Of Her-2 Expression In Primary Tumours and Metasmentioning
confidence: 99%
“…When anti-HER-2 immunotherapy such as cancer vaccination is considered for HER-2-positive patients, the candidates are restricted to a certain HLA haplotype (Kono et al, 2002a). It is important to clarify the HER-2 status relating to the HLA haplotype in patients with oesophageal SCC.…”
Section: Correlation Of Her-2 Expression In Primary Tumours and Metasmentioning
confidence: 99%
“…Strong amplification of the region 17q12-21 was reported in the intestinal type of gastric cancer. 59 Amplification and/or overexpression of some genes on chromosome 17q21.1, such as ERBB-2 (HER2/ neu) 8,9,60,61 and TOP2A (for topoisomerase IIa), 62 have been reported in gastric cancer and breast cancer, and might represent prognostic factors. Recently, an antineoplastic drug that targets the HER2 gene has been used to treat breast cancer and there are reports of overexpression of the HER2/neu gene in gastric cancer.…”
Section: Genetic Alterations In Gastric Cancermentioning
confidence: 99%
“…Recently, an antineoplastic drug that targets the HER2 gene has been used to treat breast cancer and there are reports of overexpression of the HER2/neu gene in gastric cancer. 61 Therefore, the same antineoplastic drug might be useful for the treatment of gastric cancer. It has also been reported that gain at 17q is a powerful prognostic factor and a candidate gene on 17q23 is PPM1D, whose expression is associated with prognosis in neuroblastoma.…”
Section: Genetic Alterations In Gastric Cancermentioning
confidence: 99%
“…Trastuzumab also suppresses DNA repair capacity (18) through as yet unknown pathways, contributing to the ability of the antibody to enhance the anti-tumor effect of DNA-damaging agents such as cisplatin (18) and radiotherapy (19). In vivo, trastuzumab inhibits angiogenesis and induces antibody-dependent cellular cytotoxicity (13,14), potentially contributing to its activity. Loss or blockade of the Fc␥RIII receptor on leukocytes has been shown to severely impair the anti-tumor effect of trastuzumab in vivo (15), indicating involvement of Fc-receptor-dependent mechanisms.…”
mentioning
confidence: 99%